RANCANGAN MONITORING KELEMBABAN TEMPERATUR RUANG INKUBATOR BAYI MENGGUNAKAN VISUAL BASIC & ATMEGA 16 - alfian junaidi (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2019)
Abstract— At this time many accidents in infants inincubators tube, which causes the baby has been overheated, skinburns baby until the baby died. This incident occurred because of thenegligence of the hospital employees and the absence of anotification or an application interface that tells that the temperatureon the tube incubator in bad condition.Therefore we need a device that can measure thetemperature and humidity data and transmit it whenever the observerwant to take the data and can store data in a form of a report (datareport) by utilizing the application interface.Based on that, the authors intend to create a tool to detectthe temperature and humidity in the incubator space under the titleMonitoring Temperature and humidity in the baby incubator space.This tool is used to detect the temperature and humidity in the babyincubator space, temperature and humidity sensors on the baby'sincubator space will also help the workforce (human) in carrying outits duties.